The impact of symptoms, irritable bowel syndrome pattern and diagnostic investigations on the diagnostic delay of Crohn's disease: A prospective study. Issue 8 (August 2015) - Maconi, Giovanni; Orlandini, Laura; Asthana, Anil K.; Sciurti, Roberta; Furfaro, Federica; Bezzio, Cristina; de Franchis, Roberto
Abstract Background We investigated symptoms and tests performed prior to a formal diagnosis of Crohn's disease and the reasons for diagnostic delay. Methods Consecutive patients recently diagnosed with Crohn's disease were enrolled between October 2012 and November 2013. Clinical data, symptoms including Rome III criteria at onset and at diagnosis, location and disease phenotype were recorded. Faecal calprotectin, radiological and endoscopic examinations performed prior to diagnosis were analysed. Diagnostic delay, stratified into tertiles and median time, was analysed using parametric and nonparametric tests. Results 83 patients (49.4% males, median age 31 years) were enrolled. The median diagnostic delay was 8 (0–324) months. Twenty-six patients did not consult a general practitioner until diagnosis (31.3%), 18 presented to the emergency department (21.7%) and 8 directly to a gastroenterologist (9.6%). Diagnostic delay was not associated with specific symptoms. However, patients with bloating at presentation had a longer delay compared to those who did not (median, 6.1 vs. 16.8 months, respectively; p = 0.016). Nineteen patients underwent incomplete ileocolonoscopies (22.9%) and 7 had no biopsies (8.4%), with a consequent diagnostic delay (median, 24 and 24 vs. 6 months, respectively; p = 0.025 and p = 0.008). Conclusion Diagnostic delay for Crohn's disease is significantly associated with incomplete ileocolonoscopies, but not with symptoms, except bloating at presentation.